Dual-beam room-temperature atomic magnetometer with high sensitivity and large dynamic range. (1st January 2023) - Liu, Bei; Peng, Jin; Wang, Hai-Ning; Fang, Chang-Feng; Wang, Jun-Lei; Zhao, Xian; Deng, Lu
Abstract: We demonstrate a dual-beam high-sensitivity room-temperature atomic magnetometer (AM) with a large dynamic range based on a nonlinear magneto-optical rotation (NMOR) enhancing scheme. Using an inelastic wave-mixing laser, we find significant NMOR signal enhancement compared with a single-beam scheme under the same far-detuned operation conditions. This dual-beam scheme is shown to operate well in the regime of lower laser intensity and off-resonance detuning. The best sensitivity achieved is 20 fT/Hz 1/2 with a bandwidth of 2 kHz, substantially greater than common spin-exchange relaxation-free AMs. This provides a way to develop low-power, inexpensive miniaturized AMs for wide application.